PID offline tuning using gravitational search algorithm - Ab. Ghani, Zailani (2013)
PID controller is a common controller which is applied for many applications around the world. The simple structure and less effort of tuning make this controller being chosen in industrial and many research areas. The PID controller parameters usually tune heuristically to obtain the required output performance. This method has no systematic way of tuning procedure thus make the controller parameters tuning consuming a lot of time and effort. This problem will be more complicated when the system is dynamic and the performance of output response is the priority. With motivation of this problem, the Gravitational Search Algorithm (GSA) can be developed to make the process of PID controller tuning can be more easily and has systematic procedure of tuning method.